Court-ordered assessments of family resources in family law proceedings: the technical advisor and other non-juridical professionals compared and contrasted - Cordiano, Alessandra (Italian Sociological Review, 2013)
This study provides a reconstruction of the legal framework surrounding family break-up proceedings in order to observe the overlaps in the responsibilities of and relations between the social services and the courtappointed technical advisor and the technical advisor chosen by the parties.